FINANCIAL MANAGEMENT OF SANTRIWATI - Mahbubah, Aisy Nafisatul; Prajawati, Maretha Ika (REVENUE: Jurnal Manajemen Bisnis Islam, 2024)
This research aims to analyze the financial management of female students at Islamic Boarding School Salaf Hidayatul Mubtadi'in Kembang. This qualitative research uses case studies and primary data obtained from interviews with female students at the Islamic Boarding School Salaf Hidayatul Mubtadi'in Kembang, Singosari District, Malang Regency. This research used a sample consisting of 10 female students as informants. Data was collected by interviews using random sampling techniques. The results of this research show that financial management among female students can make an individual more careful in managing their finances because they already know how to manage their emotions well in managing expenses. So they will become wiser in making decisions about using money and spending according to their needs, not according to their desires. Financial knowledge and personal finance management skills are very important in everyday life. An individual must be able to manage his own finances. Apart from that, the younger generation is a group that has a large contribution to the economy.